An investigation on selective laser melting of Al-Cu-Fe-Cr quasicrystal: From single layer to multilayers. (July 2017) - Fu, Yingqing; Kang, Nan; Liao, Hanlin; Gao, Yang; Coddet, Christian
Abstract: In this study, the effects of processing parameters on the microstructure of Al-Cu-Fe-Cr quasicrystalline (QC) coatings fabricated by selective laser melting (SLM) are investigated. A qualitative analysis on the XRD patterns indicates that the phase composition for the SLM processed coating mainly consisted of Al-Cu-Fe-Cr quasicrystals and α-Al (CuFeCr) solid solution, and with increasing laser energy input or coating thickness, the volume fraction of QC i-Al91 Fe4 Cr5 reduced and those of QC d-Al65 Cu20 Fe10 Cr5 and crystalline θ-Al2 Cu increased. The formation of cracks during the coating building procedure from single layer to multilayers is also discussed. For the coatings with the same layer number, the pores and balling particles diminish as laser power increases, due to the growth of melting degree. At the early stage of fabrication, with increment of layer number (or coating thickness), pores and balling particles decrease considerably because the molten pool solidified more "slowly". However, after the layer number increases continuously from 10 to 20, the porosity no longer decreases, and some big size pores, microcracks and fractures appear, especially for the sample obtained at lower laser power. A wavy-like pattern composed chiefly of Al and QC phases, is formed at the interfacial region between substrate and coating due to Marangoni effect. Graphical abstract: Highlights: Al-Cu-Fe-Cr quasicrystalline coatings were prepared by selective laser melting. As layer number increase, QC changes from i-Al91 Fe4 Cr5 to d-Al65 Cu20 Fe10 Cr5 . Moderate increase of laser power (layer number) can decrease coating porosity. A wavy-like structure was formed at interfacial region (substrate and coating).